Blended Learning pada Masa Pandemi Covid-19: Efektivitas Pembelajaran PJOK di SMA Kota Palu - Kamarudin Kamarudin; Ikhwan Abduh; Muhammad Agusman (Universitas Tadulako, 2023)
The problem in this research is how to use the blended learning model during the Covid-19 pandemic and the effectiveness of PJOK learning in SMA Kota Palu. This type of research is descriptive quantitative. The population is all public high schools in the city of Palu, totaling 14 schools. Research data collection techniques used are questionnaires, interviews, and documentation. The research results were analyzed using frequency distribution and cross tabulation. The findings of the research results were that of the 60 respondents who were given a questionnaire, the respondents who answered that they had never used the blended learning model were 3.3%, quite often as many as 46.7%, said often as much as 26.7%, and very often as many as 5%. In general, from a total of 60 respondents, the effectiveness of the blended learning model that was carried out was that those who answered quite effectively were 45%, effective 28.3%, the rest were divided into other categories which stated that the blended learning model was very effective by 5%, not effective by 15 %, and very ineffective at 6.7%. From the results of this analysis, it can be concluded that in terms of the use of the blended learning model it is used quite often and in terms of the effectiveness of the blended learning model it is quite effective.